Optimalisasi Pengawasan Koperasi Dalam Perlindungan HukumDebitur dan Keberlanjutan Layanan Simpan Pinjam - Agus Salim, (Proceeding International Conference on Social Sciences, 2026)
Koperasi Simpan Pinjam (KSP) has a strategic role in Indonesia's economy as a Lembaga keuangan non-bank that provides savings and loan services to the public. This study aims to analyze the supervisory mechanism of Koperasi Simpan Pinjam in Indonesia and to examine the legal protection for debtors within the sistem Koperasi Simpan Pinjam. The research method used is normative legal research with a statutory approach and a contextual approach. Data were collected through literature review by analyzing statutes, legal literature, and related scientific journals. The results show that supervision of KSP is conducted through two lines, namely internal supervision by the Badan Pengawas Koperasi and external supervision by the Kementerian Koperasi dan UKM and the Otoritas Jasa Keuangan (OJK). Legal protection for debitur KSP is regulated in various laws including UU No. 25 Tahun 1992 tentang Perkoperasian, PP No. 9 Tahun 1995, and consumer protection provisions. However, in practice, there are still weaknesses in the implementation of supervision and law enforcement that may harm debtors. This study recommends strengthening coordination between supervisory agencies and increasing legal awareness among cooperative members.